The role of maternal echocardiography and uterine artery Doppler at 11-14 weeks in the prediction of pre-eclampsia in nulliparous women - Sah, Dipak K.; Deeba, Farzana; Chowdhury, Saleha B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pre-eclampsia (PE) complicates 2% of pregnancies and may have serious effects on mother and child, which makes it an important threat to public health in both developed and developing countries. Once high-risk women are identified, they can be targeted for more intense prenatal surveillance and preventative measures. Predicting PE in the first trimester requires the use of maternal echocardiography and the uterine artery pulsatility index (UAPI). Objective of the study was to see whether maternal echocardiography and uterine artery Doppler at 11-14 weeks can predict subsequent development of PE in nulliparous women. Methods: This prospective observational cohort study was carried out in outdoor patients of obstetrics and gynecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), with collaboration with department of cardiology, National Institute of Nuclear Medicine and Allied Sciences (NINMAS), BSMMU, Dhaka, during 01 December 2013 to July 2015. A total of 135 healthy nulliparous women at 11-14 weeks of gestation were included in this study. Data was processed and analyzed by statistical package for the social sciences (SPSS) version 24.0. Results: Among 135 patients, two (1.5%) patients developed preeclampsia during 1st follow-up (20-28 weeks) and four (2.9%) patients developed preeclampsia during (29-36 weeks). Mean total peripheral resistance was found to be 1332.0±75.2 dynes/sec/cm5 in preeclampsia and 1157.0±139.2 dynes/sec/cm5 in non preeclamptic pregnancy. The difference between two groups was statistically significant. MAP and total peripheral resistance were statistically significant (p<0.05) between two groups. Conclusions: In first trimester of pregnancy UAPI is the best predictor for detection of PE.